2020
DOI: 10.1002/jssc.202000594
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of capillary electrophoresis‐frontal analysis for displacement studies: Effect of several drugs on l‐tryptophan and lidocaine binding to human serum albumin

Abstract: The effective concentration of a drug in the blood, i.e. the concentration of a free drug in the blood, is influenced by the strength of drug binding onto plasma proteins. Besides its efficacy, these interactions subsequently influence the liberation, absorption, distribution, metabolism, excretion, and toxicological properties of the drug. It is important to not only determine the binding strength and stoichiometry, but also the binding site of a drug on the plasma protein molecule, because the co-administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Table 5 showed different studies that have been reported over the years for the evaluation of the binding affinity of HSA of numerous drugs and other bioactive compounds using CE techniques. Many studies focused on the individual binding parameters for each compound/enantiomer [153,155,161] while others also described competitive studies between compounds to the binding sites of HSA [156,157,159]. Furthermore, most of these studies were enantioselective studies where the differences in binding of each enantiomer of the analyzed compounds to HSA were evaluated and compared using, many of them, HSA as a chiral selector [150,152,154,155].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
See 4 more Smart Citations
“…Table 5 showed different studies that have been reported over the years for the evaluation of the binding affinity of HSA of numerous drugs and other bioactive compounds using CE techniques. Many studies focused on the individual binding parameters for each compound/enantiomer [153,155,161] while others also described competitive studies between compounds to the binding sites of HSA [156,157,159]. Furthermore, most of these studies were enantioselective studies where the differences in binding of each enantiomer of the analyzed compounds to HSA were evaluated and compared using, many of them, HSA as a chiral selector [150,152,154,155].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…The results showed that the (S)-amlodipine binds to HSA more strongly (0.902-1.04 × 10 5 M −1 ) than its antipode (0.991-1.12 × 10 4 M −1 ) [151]. CE-FA was also used to study the binding of L-tryptophan and lidocaine to HSA as well as the effect of several drugs on the binding affinity through displacement studies [159]. A decrease in the bound of L-tryptophan was observed in the presence of the other drugs indicating that these molecules share the same binding site while no difference was observed for lidocaine [159].…”
Section: Capillary Electrophoresismentioning
confidence: 99%
See 3 more Smart Citations